ROP Modelling, Analysis and Optimization Study Based on Morvin Field 6506/11 Drilling Data. - Mohamud, Yahya Ibrahin Hassan (University of Stavanger, Norway, 2020)
Master's thesis in Petroleum engineering. During the planning phase, the drilling rate of penetration (ROP) optimization simulation studies are performed in order to increase ROP, reduce the drilling time - and bit wear. Optimizing ROP is important to improve the overall drilling performance and reduce operational costs. This thesis presents the ROP modelling based on the drilling data obtained from Morvin Field 6506/11 in the Norwegian Sea. The models used for the assessment were Multiple regression, MSE, D-exp, Warren and Bourgoyne & Young models. The modelling approaches were based on the entire well data, hole sections and geological groups. Furthermore, the models were tested on its own, nearby and far-away wells. Finally, modelling and drilling ahead ROP predictions on its own well were also tested. Results show that the model predictions are good enough when applying on the wells they are derived from. The degree of the prediction reduces when applying on far away wells. It was also found out that the modelling and application on the drilling ahead approach works well. From the evaluation, it was observed that using 90% of the data for the modelling predicts the 10% of the drilling ahead quite well. Out of the considered modelling scenarios, modelling based on the geological groups provided the best results. Moreover, in this thesis, the Bourgoyne & Young model was modified to include more drilling parameters. The modelling and application results showed better prediction.